2018
DOI: 10.1007/s40620-018-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab in pregnancy: a narrative overview

Abstract: Pregnancy can be a dangerous trigger for patients with paroxysmal nocturnal hemoglobinuria (PNH), atypical hemolytic uremic syndrome (aHUS), or hemolysis, elevated liver enzymes and low platelet (HELLP) syndrome. Due to the possibility of several serious complications, pregnancy is somewhat discouraged in the presence of the above diseases. Eculizumab is a humanized antibody that may dramatically change the clinical course of PNH, aHUS and HELLP syndrome. However, data on the safety of eculizumab in pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Eculizumab, a monoclonal antibody inhibitor of C5, reduces the generation of complement components C5a and C5b-9 and their downstream effects. Eculizumab appears to be safe in pregnancy as demonstrated by its use in paroxysmal nocturnal hemoglobinuria18 19 and atypical hemolytic uremic syndrome (aHUS) 19–21…”
Section: Discussionmentioning
confidence: 99%
“…Eculizumab, a monoclonal antibody inhibitor of C5, reduces the generation of complement components C5a and C5b-9 and their downstream effects. Eculizumab appears to be safe in pregnancy as demonstrated by its use in paroxysmal nocturnal hemoglobinuria18 19 and atypical hemolytic uremic syndrome (aHUS) 19–21…”
Section: Discussionmentioning
confidence: 99%
“…The advent of eculizumab has the potential to dramatically improve the outcome of this highly morbid disease 9. Eculizumab is a humanised monoclonal antibody that blocks the cleavage of the terminal complement protein C5 preventing formation of MAC10 and has been used to treat P-aHUS with improvement in haematological and renal parameters in a patient who carried heterozygous mutations in the CFH and CFI genes 11.…”
Section: Discussionmentioning
confidence: 99%
“…48 There are multiple cases of normal complement levels in exposed newborns. 47,49,50 It has also been suggested that low complement levels may be related to prematurity associated with the underlying disease. 51,52 Further data are needed to conclusively determine whether this drug is safe to be used during pregnancy.…”
Section: Hyperhemolysis Prophylaxismentioning
confidence: 99%